The Preparation of Stable MoS2 Dispersions by Using Well-Defined Polymers with Pendant Sulfide Moieties - Jin Motoyanagi; Kohei Kawade; Masahiko Minoda (Chemistry)
The preparation of stable dispersions of MoS2 by ultrasonic aqueous and/or organic media containing amphiphilic molecules is an attractive and widely applicable method to form MoS2 fine particles while suppressing its aggregation. In this study, we developed a series of polymers with pendant sulfide moieties as a new dispersant, under the hypothesis that it would interact with sulfur atoms on MoS2 surfaces. First, we designed a sulfide group-substituted methacrylate derivative (ESMA) with the hypothesis that it would interact with the MoS2 surface through sulfur-sulfur interactions. Then, we synthesized well-defined polymers with pendant sulfide groups by living radical polymerization (ATRP). Next, 0.5 wt% MoS2 was added to a DMSO solution containing 1 wt% of the obtained polymer (polyESMA), and the mixture was treated with a bath-type ultrasonicator for 3 h to obtain a MoS2 dispersion. We found that stable dispersions of MoS2 in a fine particle state, although not in the form of single-layer or few-layer nanosheets, could be readily formed in DMSO using polyESMA as a polymeric dispersant. Furthermore, we synthesized polymeric dispersants with different molecular weights and investigated the relationship between the structure of the dispersant and the dispersion stability.